Octatonicism and Chromatic Harmony - Boulay, Jean-Michel (Canadian University Music Review / Revue de musique des universités canadiennes)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 1996)
In this paper, the author looks at the relationship between octatonic structures and chromatic harmony. The discussion concentrates on two major aspects of late-tonal octatonicism: the use of alternative bass tones for the diminished seventh chord and the development of these sonorities into hexachordal and pentachordal combination chords. A number of late nineteenth-century and early twentieth-century chromatic passages are analyzed. Complex harmonies in chromatic passages are explained by formulating reductive models comprised of simpler, octatonic constructs.